Analisis Minat dan Perilaku Perjalanan Wisata pada Generasi Z Ke Obyek Wisata Berastagi - Sri Indrayanti; Hilda Sari Wardhani; Gatot Harry Purnomo (CV. Creative Tugu Pena, 2024)
The aim of this research is to analyze the interests and travel behavior of generation Z by considering several reasons for choosing a tourist destination to Berastagi. This research uses a quantitative method which obtains data through distributing questionnaires online to 130 respondents belonging to generation Z. In analyzing the data, researchers applied the interval distribution method. The results of this research found that generation Z's interest and behavior in traveling to the city of Berastagi is based on curiosity, trying new things and recommendations. Meanwhile, the behavior obtained from this research is awareness of needs and evaluation. It is hoped that this research will provide input and insight for the industry in the tourism sector and local government as well as the community who have an interest in developing, organizing and managing the Berastagi City Tourist Destination Area to attract Generation Z's interest in visiting there.